Modelling the sub-100 fs Dy3+: Fluoride fiber laser beyond 3 μm. (February 2023) - Li, Guolong; Ma, Chunyang; Peng, Jie; Liu, Jun; Zhao, Chujun; Tang, Pinghua
Highlights: Laser performances for all kinds of mode-locking schemes of the Dy 3+ : fluoride fiber laser have been compared by numerical investigation. Sub-100 fs generation in the Dy 3+ : fluoride fiber laser beyond 3 μm via the hybrid mode-locking mechanism with dispersion compensation has been demonstrated. Laser performance optimizations have been investigated. Abstract: Generating ultrafast pulses in the mid-infrared (mid-IR) region around 3 μm is a scientific and technological frontier at present. In this work, we have investigated the sub-100 fs Dy 3+ : fluoride fiber laser generation beyond 3 μm regime via the hybrid mode-locking mechanism based on the semiconductor saturable absorber mirror (SESAM) and the nonlinear polarization rotation (NPR) method numerically. Compared with the single SESAM- and NPR-based mode-locking, the hybrid mode-locked Dy 3+ : fluoride fiber laser delivers much shorter pulses via the fast and slow mode-locking from the NPR and SESAM, respectively. When dispersion compensation is taken into the hybrid mode-locking, the ultrafast pulse of 94 fs with a corresponding time-bandwidth product (TBP) of 0.333 is achieved. In addition, laser performance optimizations are investigated. By optimizing the parameters of the gain fiber and SESAM, the shortest pulse duration of 85 fs can be obtained. The results represent a feasible solution and design guidelines for ultrafast mid-infrared fiber laser generation beyond 3 μm.